2013
DOI: 10.1108/ijebr-10-2012-0106
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation in small firms – values-attitudes-behavior approach

Abstract: Purpose -The purpose of this paper is to examine the antecedents of entrepreneurial orientation (EO) and also apply the values-attitudes-behavior framework in the context of entrepreneurial behavior. Design/methodology/approach -A quantitative approach is used to test the hypothesis. The paper employs empirical survey data and partial least squares path modeling in the analyses. Findings -The analyses reveal that owner-manager's intrinsic work values are strongest drivers of innovative and proactive behaviors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 104 publications
1
11
0
Order By: Relevance
“…The craftsman is described by low social engagement, as well as a desire for autonomy, and not financial or status achievements when starting a business. At the other side, an opportunist entrepreneur has a greater desire for profit and growth, and a future-oriented orientation (Soininen et al, 2013). This typology implies that the dimension of social awareness and social engagement is important in determining the personality of the entrepreneur.…”
Section: Entrepreneurial Intention and Social And Political Awarenessmentioning
confidence: 99%
See 1 more Smart Citation
“…The craftsman is described by low social engagement, as well as a desire for autonomy, and not financial or status achievements when starting a business. At the other side, an opportunist entrepreneur has a greater desire for profit and growth, and a future-oriented orientation (Soininen et al, 2013). This typology implies that the dimension of social awareness and social engagement is important in determining the personality of the entrepreneur.…”
Section: Entrepreneurial Intention and Social And Political Awarenessmentioning
confidence: 99%
“…However, taking into account the various activities of social engagement that determine the differences in the personality of an individual, it is possible to expect different effects on the EI. Some studies suggested that extrinsic and social work values may be negatively associated with entrepreneurially oriented behavior (Soininen et al, 2013).…”
Section: Entrepreneurial Intention and Social And Political Awarenessmentioning
confidence: 99%
“…The cross-cultural differences of EO were also investigated (Thomas and Mueller, 2000; Wolff et al, 2015); the study discovered that for some cultures EO is considered a positive catalyst for business growth, whereas other cultures have a negative EO perception. Referring to the positive effects, the EO was considered a creative destruction (Schumpeter, 1934) connected to an entrepreneurial posture (Covin and Slevin, 1990; Sakari Soininen et al, 2013; Stewart et al, 2016) and entrepreneurial style (Naman and Slevin, 1993). EO was recognized as a catalyst of an entrepreneurial team formation (Clarysse and Moray, 2004) and identified as a driver for spin-off performance (Clarysse and Moray, 2004; O’Shea et al, 2005; Vohora et al, 2004; Walter et al, 2006).…”
Section: Eo and Spin-offmentioning
confidence: 99%
“…Entrepreneurial behaviours are commonly understood as being driven by a relatively narrow, but essential, set of traits, for example, high tolerance for, and engagement with, risk; a strong desire for personal autonomy; a vision for opportunity seeking; and the capacity to innovate (Soininen et al 2013). In turn, there are associated benchmarks for what constitutes 'success', for example, high growth; profit as motivator; business on a global scale; and multiple business ownership (Gorgievski et al 2011).…”
Section: Public Narratives Of Entrepreneurshipmentioning
confidence: 99%